The Impact of Differentiated Learning Strategies on Student Engagement and Achievement - EREKAT, HEBAH DAOUD SALEEM (2025)
This dissertation looks at how different teaching strategies affect middle school students' academic performance and involvement. Differentiating instruction and evaluation to every student's particular need helps to create a friendly and dynamic environment. This study fills a gap by providing empirical evidence of its effectiveness during middle school, a crucial developmental period. A teacher survey, department head and coordinator interviews, and classroom observations were among the mixed-methods data collecting tools used. While the qualitative observations recorded real-time practices, the quantitative data exposed trends. Studies show that, when done correctly, differentiation increases student performance and involvement. Important practices are flexible groupings, tiered assignments, and a range of assessments. Success depends critically on cooperation, the availability of resources, and teacher development, while two challenges are the time constraints and inconsistent training.